Escolas como organizações que aprendem: a autoavaliação moduladora da aprendizagem da escola - Moura, Elton Oliveira de (2021)
This thesis dissertation aimed to analyze how the practice of school self-assessment acts as a modulating element of school learning. The onto-epistemology of the Theories of Practice was adopted from the sociological perspective of Learning Organizations. The argument of this thesis is based on two assumptions: (1) the school is an organization that learns from its daily practices, and (2) that self-assessment can be a way to the development of school learning. The empirical study had a first exploratory phase, where some specialists and professionals in educational management were interviewed to foster reflections on the evaluation and learning processes of the school. In the second moment, empirical research was conducted in a public elementary and high school in the city of João Pessoa (PB) in northeastern Brazil. Data collection was driven through online interviews with participants from the school community, remote observations, and documents. Because the research was conducted during the Covid-19 pandemic, digital technologies such as video conferencing and messaging applications mediated the data collection process. The data analysis process adopted the framework proposed by Bispo (2015) to analyze research based on practice. The study's main results indicate that school learning occurs from three practices: self-assessment learning, engagement in practice, and translating policies and context. In addition, it was possible to verify that selfassessment acts as a modulating element of school learning to the point that it balances the relationship between concept ("what") and instrument ("how"). School self-assessment as a modulator of learning is based on the idea that reflection on the practices allows the school to direct more appropriate actions to its specific needs. This research contributes to approximate fields of Administration and Education to develop an expanded understanding of studies on school management and educational management. Also, in building the development of an alternative approach to the study of Schools as Learning Organizations from social learning. Last, in thinking possibilities of evaluation less classificatory, less focused on accountability, and more focused on school learning.